WINTER WHEAT (TRITICUM AESTIVUM L.) CELL CULTURES AS A MODEL SYSTEM FOR STUDYING - Bronnikova, L. I.; Khomenko, L.; Dikun, M. (НДУ ім. М. Гоголя, 2025)
Random changes, especially stress, cause plants to undergo significant metabolic and structural modifications. Most of these are adaptive responses that make the organism more suited to new conditions. Salinisation is the most harmful abiotic stress. In the case of severe stress, the effectiveness of the genotype’s vital functions becomes apparent over a long period of time. Cell culture allows us to avoid problems: physiological, biochemical, and other changes that occurred due to the stressor. The aim of this study was to analyse the content of free proline and protein in different cell cultures of wheat varieties subjected to prolonged osmotic stress. However, the accumulation of this osmolyte alone cannot serve as an indicator of successful adaptation. Under conditions of severe stress, which significantly limits the availability of external trophic and energy resources, proline can act as a reserve source of nitrogen and carbon. Therefore, the Pro pool in cells subjected to prolonged stress can change significantly. When studying the dynamics of changes in wheat plants, we found that the level of proline in callus cells in the Volodarka variety decreased as stress pressure increased, and the synchronous decrease in amino acid content during prolonged salt stress in the Zolotokolos and Smuglyanka varieties was 18.3 ± 3.4% and 21.4 ± 4.6%, respectively. In wheat, reserve proteins (gliadin and glutenin) belong to this category of proteins. In wheat grains, they account for 75-85% of the total protein composition; the gliadin/glutenin ratio depends on the specific variety or genotype of the plant. In addition, these proteins are rich in arginine and glutamine. The remaining part of the endosperm proteins consists of albumins and globulins, many of which have enzymatic activity. We observed a significant depletion of the protein pool, independent of the type of salinity. Since glutenin is also enriched with proline, the increase in the content of this amino acid in cells during salinisation could be the result of their hydrolysis. Indirect evidence of this may be the decrease in osmolyte content on the 25th day. The progressive decline in glutenin reserves led to a decrease in proline.
Keywords: salinisation; proline; protein; winter wheat; cell selection